Biomonitoring Kesehatan Kerang Abalone (Haliotis squamata) Hasil Tangkap di Perairan Mengening, Bali Dengan Pengamatan pada Aktifitas Fagositosisnya - Ulinuha, Devi; Perwira, Ima Yudha (Journal of Marine and Aquatic Sciences; Vol 5 No 1 (2019), 2018)
The health level of captive abalone ( Haliotis squamata ) in Mengening waters, Bali Island, was observed through observation on the phagocytosis activities. This study was aimed to determine the health level of abalone in the Mengening waters influenced by their environmental factors. The method is in this study was descriptive, through observation on any parameters of the immunity including: Total hemocyte count (THC) and Percentage of Fagocytosis. Water quality in the location was also measured, including Dissolved Oxygen (DO), pH, water temperature, and water salinity. THC of Abalone in Mengening waters was 2.03 x 10 6 celss/ml, while the percentage of phagocytosis was 75,9%. Water quality during the study showed optimal condition (DO: 5.9-6.1 ppm; pH: 7.8; water temperature: 25.1-31.5 o C; and water salinity: 33-34 ppt), even there was fluctuation on the water temperature (>5 o C) between morning and afternoon.